Efficient dynamic mechanisms with interdependent valuations - HE, Wei (Institutional Knowledge at Singapore Management University, 2016)
This paper considers a dynamic environment with interdependent valuations and evolving private information. Under the assumption of “independent types”, we construct an efficient, incentive-compatible mechanism that is also budget-balanced in every period of the game. Our mechanism works in environments where in each period, each agent observes her own realized outcome-decision payoff from the previous period. This extends the insight of Mezzetti (2004) to the dynamic setting.